Pembelajaran Kolaboratif Berbasis Guided Inquiry melalui Lesson Study pada Materi Listrik Dinamis - Cindy Aulia Phadila; Challilullah; Andinie Novrida Ramadhani; Tika Yuli Yanti; Iqbal Kurniady; Nova Susanti; Neneng Lestari (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Physics learning on dynamic electricity material still faces problems related to low student participation and collaborative skills during the learning process. This study aims to describe the implementation of lesson study in collaborative learning using the guided inquiry model on dynamic electricity material to improve students’ collaborative skills. The study employed a quantitative descriptive approach involving 17 Physics Education students divided into four learning groups. The lesson study activities were carried out through three stages, namely plan, do, and see. The research instrument consisted of an observation sheet of collaborative skills with 15 assessment indicators using a 1–4 scale. The data were analyzed using quantitative descriptive techniques in the form of percentages. The results showed that the average collaborative skill of students reached 71.57% in the good category. The highest indicators were found in helping peers and open communication, while the lowest indicator was providing support to group members. The implementation of the guided inquiry model through practicum activities increased students’ activeness, interaction, and cooperation during the learning process. Therefore, the integration of lesson study and guided inquiry-based collaborative learning is effective in improving students’ collaborative skills in physics learning, especially on dynamic electricity material.